Утопленник с приветом: повесть / Елена Александровна Усачева, Елена Александровна - Усачева Елена Александровна (Серяи "Кошмарики", 2006)
Экземпляры: Селтинская районная библиотека (аб) (20191026) / Инвентарный номер: 192007 / Цена: / Авт.знак: У74 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6